Landfill closures : geosynthetics, interface friction, and new developments - Koerner, Robert M., 1933- (Elsevier Applied Science, 1991)
The closure [capping] of completed or abandoned solid waste facilities present particular challenges, for example: & starf; there usually exists a very uncertain and random subsidence behaviour of the existing waste beneath the closure, & starf; the friction behaviour of the various interfaces that are involved in solid waste facilities is not established, & starf; there are numerous long term geosynthetic stability and durability issues that must be addressed, and & starf; there are an extremely large number of sites that require proper closure. These topics are addressed in the three sessions.